Etravirine as a Switching Option for Patients with HIV RNA Suppression: A Review of Recent Trials. (25th February 2014) - Nelson, Mark; Hill, Andrew; van Delft, Yvon; Moecklinghoff, Christiane
Abstract : Unlike other nonnucleoside reverse transcriptase inhibitors, etravirine is only approved for use in treatment-experienced patients. In the DUET 1 and 2 trials, 1203 highly treatment-experienced patients were randomized to etravirine or placebo, in combination with darunavir/ritonavir and optimized background treatment. In these trials, etravirine showed significantly higher rates of HIV RNA suppression when compared with placebo (61% versus 40% at Week 48). There was no significant rise of lipids or neuropsychiatric adverse events, but there was an increase in the risk of rash with etravirine treatment. In the SENSE trial, which evaluated etravirine and efavirenz in 157 treatment-naïve patients in combination with 2 nucleoside analogues, there was a lower risk of lipid elevations and neuropsychiatric adverse events with etravirine when compared to efavirenz. Etravirine has been evaluated in three randomized switching studies. In the SSAT029 switch trial, 38 patients who had neuropsychiatric adverse events possibly related to efavirenz showed an improvement in these after switching to etravirine. The Swiss Switch-EE recruited 58 individuals without neuropsychiatric adverse events who were receiving efavirenz, and no benefit was shown when switching to etravirine. In the Spanish ETRA-SWITCH trial (n = 46 ), there were improvements in lipids when individuals switched from a protease inhibitor to etravirine. These switching trials were conducted in patients with full HIV RNA suppression: <50 copies/mL and with no history of virological failure or resistance to therapy. The results from these three randomized switching studies suggest a possible new role for etravirine, in combination with two nucleoside analogues, as a switching option for those with HIV RNA suppression but who are reporting adverse events possibly related to antiretroviral therapy. However a large well-powered trial would need to be conducted to strengthen the evidence from the pilot studies conducted so far.